Eating Disorders in Athletes – A Review - Matuszewska, Julia; Poręba, Kacper; Poręba, Martyna; Jakubowska, Paulina; Rusiłowicz, Rafał; Peszt, Michał Józef; Prokopczyk, Kamila; Wasilczuk, Antoni; Szaryński, Mikołaj; Lewandowska-Mackiewicz , Aleksandra (Quality in Sport, 2025)
Introduction The aim of this review is to synthesize evidence on eating disorders (ED) in athletes, including prevalence, risk factors, diagnostic challenges, clinical outcomes, and management strategies in the context of sports medicine and public health. Materials and Methods The analysis is based on epidemiological, clinical, and experimental studies on ED in athlete populations, with particular focus on aesthetic, endurance, and weight-category sports, which carry the highest risk of developing eating disorders. Main Findings Data indicate that the prevalence of ED in some athlete groups may reach up to 40%, with men accounting for approximately one-quarter of diagnoses, often presenting symptoms oriented toward leanness and muscularity, which contributes to underdiagnosis. Low energy availability (LEA) and relative energy deficiency in sport (RED-S) are central mechanisms leading to hormonal, skeletal, and cardiovascular dysfunction, increased injury risk, and delayed recovery. Diagnostic challenges stem from normalization of restrictive behaviors, underreporting of symptoms, and limited validity of standard screening tools in athletic populations. Conclusions Effective clinical management requires multidisciplinary care, early recognition of “red flags,” sport-specific diagnostic approaches, and individually tailored dietary, psychological, and organizational interventions. Preventive strategies should include coach education, reduction of appearance-related pressure, and stigma mitigation to decrease the burden of eating disorders among athletes.